AB0821 Early detection of the changes in pulmonary arterial pressure and vascular functions in systemic sclerosis: exploring non-invasive clinical test methods and underlying gene expressions. (12th June 2018) - Koyama, Y.; Fuke, S.; Ohno, T.; Sato, Y.; Higuchi, T.
Abstract : Background: Pulmonary arterial hypertension (PAH) is prominent as a vascular involvement in systemic sclerosis (SSc), which remains a leading cause of death in spite of current best treatments. Although recent studies focused on early diagnosis of established PAH, it is known that more than a half of the pulmonary circulation is impaired before early PAH is detected. However, there is little study about the changes of vascular functions or the underlying gene expressions during its subclinical stage. Objectives: I. To detect the pathological changes in pulmonary arterial pressure (PAP) and vascular functions before PAH is manifested. II. To explore the changes in its underlying gene expressions of peripheral blood. Methods: Total of 103 cases without PAH symptoms (NYHA I) with either Raynaud phenomenon (RP: n=87), skin sclerosis (n=65) or SSc-related autoantibody (n=68) were enrolled. To detect the pathological change of PAP, exercise Doppler echocardiography was carried out, and exercise induced pulmonary hypertension (exPH) group was segregated from normal response group (exN) with using the definition described in R. Naeije et al. 1) Vascular function was evaluated with thermography after 0°C-stress and determination of ankle-brachial index (ABI) and cardio-ankle vascular index (CAVI). Furthermore, reactive hyperemic index (RHI), augmentation index (AI) and second derivative of photoplethsmogram ageing index (SDPTGAI) were assessed with using EndoPAT. Micro-vascular changes were also recorded with nailfold videocapillaroscopy. Meanwhile, genome-wide gene expression analysis was performed with using whole peripheral blood. The genes correlated with each vascular function tests were analysed by weighted gene co-expression network analysis (WGCNA) and pathway enrichment analysis (PathVisio). Results: There were significant differences between exPH and exN group in the result of thermography after 0°C-stress test, CAVI and AI normalised to heart rate of 75bpm (AI@75bpm). As the CAVI and AI are known to correlate positively with age, careful interpretation was necessary because the mean age of exPH group was higher as compare with exN group (69.05±11.04 vs. 60.23±14.73). However, the fact that recovery of blood-flow from RP was significantly delayed in exPH group suggested the additional pathological changes of vascular and endothelial functions. Gene expression analysis revealed that several mutual pathways such as "type2 interferon signalling", "oxidative damage" and "fatty acid omega oxidation" seemed to underlie some vascular changes. Conclusions: The results of vascular function tests including thermography after 0°C-stress, CAVI and AI@75bpm were significantly different between exPH and exN group. On the other hand, gene expression analysis showed that many factors such as ageing, arteriosclerotic and immunological mechanisms were involved in the changes of these vascular functions. Although further prospective study is required to select appropriate set of the tests, it is possible that evaluation of these vascular functions may be useful as a non-invasive test to assess the pulmonary vascular disease before PAH is manifested. Reference: [1] . R. Naeije, et al., Am J Respir Crit Care Med187, 576–583 (2013). Disclosure of Interest: None declared